Distributed Dynamic Event-Triggered Circle Formation Control for Multi-agent Systems Subject to Resource Constrained - Jia, Weibo; Wen, Jiayan; Xie, Guangming (Chinese Control Conference, 2024)
This paper investigates the issue of circle formation control for multi-agent systems subject to resource constrained. A distributed dynamic event-triggered control strategy is introduced to reduce communication frequency. This strategy involves creating an auxiliary dynamic variable for each agent to manage its triggering condition. In contrast to many current event-triggered strategies for circle formation, the proposed dynamic strategy can lead to longer average inter-event times, resulting in fewer total released instants. In addition, Zeno behavior is essentially excluded. Two numerical examples are provided to demonstrate the effectiveness of the proposed strategy.